Business and Governance in South Africa
XIV, 274 p.
Keywords: The authors identify conditions under which firms seek higher rather than lower regulation in a context of weak regulatory capacities by engaging in self-regulation or partnering up with the government and/or NGOs. They analyse how firms in the automotive, food, textile, and mining sectors fight environmental pollution and HIV/AIDS.